Identity leadership and employees’ creative performance: a serial mediation model of relational energy and organizational embeddedness - Jung, Ki Baek; Kang, Seung-Wan; Choi, Suk Bong (Frontiers in Psychology, 2025)
IntroductionThe aim of this study is to examine the relationship between identity leadership and creative performance. This study also examines the mediating roles of relational energy and organizational embeddedness in this causal relationship. Furthermore, a serial mediation model is applied, expecting that identity leadership will enhance the creative performance of organizational members through serial mediation paths.MethodsAn empirical analysis was conducted with 397 employees working in Korean manufacturing and service firms. We conducted a confirmatory factor analysis to test result validity and used hierarchical regression to examine the direct and mediating effects. Additionally, we also used the Hayes (2013) Process Macro model to test a serial mediating effect.ResultsThe results showed that identity leadership was positively related to creative performance. Relational energy and organizational embeddedness mediated the relationship between identity leadership and creative performance. Last, identity leadership increased relational energy, enhancing organizational embeddedness and leading to higher creative performance through a serial mediation effect.DiscussionOur findings confirmed the role of leaders in enhancing the creative performance of employees. Furthermore, our empirical results revealed specific pathways through which identity leadership influences employee attitudes and performance. In doing so, we contribute to the body of research on leadership and social identity theory. Finally, we provide practical implications for managers who want to facilitate employee creative performance.